Pengaruh layout Toko Retail terhadap Kepuasan Pelanggan pada Homedecor Bandung, Indonesia - Anggraeni, Syifa Nur (International Journal Administration, Business & Organization, 2023)
This study aims to determine the magnitude of the influence of the layout of the retail store at the Homedecor Bandung store on consumer satisfaction when shopping. The layout in the store will make consumers feel comfortable when shopping. Respondents obtained are consumers or people around the city of Bandung who have visited or shopped at Homedecor Bandung. In completing the research results, the research method chosen is a quantitative descriptive method with several validity, reliability, normality tests with data analysis using simple linear regression. The samples collected were 100 respondents. Technical data collection using a questionnaire distributed to respondents randomly. The results showed that the layout of retail stores, especially Homedecor Bandung, was very significant with consumer satisfaction. This shows that the layout of the retail store will affect the shopping satisfaction of its consumers. Keywords: retail store, layout, consumer satisfaction